Anglo-American Multinationals in Europe: The Curious Case of Hudson’s Bay Company Taking over Galeria Kaufhof - Gebert, Raoul (Relations industrielles / Industrial Relations, 2019)
Multinational corporations are undeniably the driving force of globalization and regional economic integration. A convenient institutional framework (Hall and Soskice, 2001) to apply when comparing multinationals from different host countries is the well-travelled road of dividing capitalist economies into coordinated market economies (CMEs) and liberal market economies (LMEs). This article aims to elucidate the tensions between centralized human resources practices and labour union avoidance usually exhibited by multinationals from so-called Liberal Market Economies (LMEs) when they expand into coordinated ones (CMEs). Specifically, it examines the recent acquisition of the German retail giant Galeria Kaufhof by the Canadian multinational Hudson’s Bay Company (HBC).The article shows that HBC has settled into an uneasy acceptance of the CME institutions, while its investment motives vacillate between a long-term, market-enlargement strategy and a short- to medium-term one, based on the rapidly increasing real estate value of its downtown flagship stores. The article encourages researchers in IR to retain three principal conclusions for the literature and for further study. First, without predetermining outcomes by looking at host-country or home-country effects alone, institutionalist frameworks do present a convenient backdrop for conceptualizing movements of multinationals across jurisdictions. Secondly, concepts such as bricolage, recombining of institutional elements and institutional entrepreneurship, stemming from the institutional change literature, should routinely figure in one’s analytical toolbox, in any attempt at non-deterministic institutional analysis. Finally, sector-level actors, such as trade unions and employers’ associations, can play an essential role in any successful adaptation of collective bargaining institutions in the context of globalization by developing, maintaining and carefully utilizing their repertoire of strategic capabilities.